GAYA KEPEMIMPINAN Dr . ABD AZIZ, M.Ag - Nuntupa; Farich Purwantoro; Rofi'atul Islamiyah (Al-Fikru : Jurnal Pendidikan Dan Sains, 2021)
The leadership of a leader always colors the process of organizing the activities of every organization, including organizations in educational units based on the vision, mission, goals and objectives set. Even the success of an organization or its failure is largely determined by the leadership style that is displayed in the organization. A leader must have his own unique and distinctive traits, habits, character and personality so that his behavior and style distinguishes him from others. The essence of the situational leadership style is actually a combined style of various existing leadership styles. The argument used in the discussion of leadership styles is that there is no one leadership style that can be applied to all situations. In fact, the application of the leadership style will be effective, if it is in accordance with the situation at hand, the leadership styles discussed are the charismatic leadership style, the transactional style and the transformational style of the figure of Dr. Abd. Aziz Wahab M.Ag. Keywords: Leader, Leadership Style